Perception of career goal attainability and its relation to self-esteem, hardy personality and locus of control among fourth year high school students - Laurente, Red Dawn Joy D.
This study sought to describe the perceptions of career goal attainability of fourth year high school students according to sex and academic curriculum. This research also examined if perception of attainability of career goals (PA) is related to self-self esteem, hardy personality and locus control. Sixty (60) randomly selected fourth year high school students enrolled in Antique National School, Province of Antique served as respondents in this study. Thirty (30 of them came from the revised Special Science Curriculum, (SSC), another the other half belonged to the Revised Basic Education Curriculum (RBEC). Each group is composed of fifteen (15) males and fifteen (15) females. The descriptive method of investigation was employed. Data were obtained using the questionnaire-checklist and evaluated using scales : Rosenberg Self-Esteem Scale, PVSIII R hardy Personality Questionnaire, Rotter?s Locus control Scale and Perceived attainability of career goal questionnaire which was constructed by the researchers for the purpose of this study.